PENDAMPINGAN USAHA MAHASISWA DALAM BERWIRAUSAHA DI UNIVERSITAS JENDERAL SOEDIRMAN PURWOKERTO - Suryanto Suryanto; Ekaningtyas Widiastuti; Sugito Sugito (Dinamika Journal : Pengabdian Masyarakat, 2020)
The Entrepreneurial Student Program at Jenderal Soedirman University has been running since 2011. Students are trained to learn entrepreneurship by being provided with various facilities such as venture capital, grants, entrepreneurship training and business assistance. Students are given the opportunity to practice entrepreneurship in a variety of businesses such as culinary, various kinds of cultivation, trade and others. Business assistance for student business groups is carried out by lecturers appointed by the Chancellor’s Decree. The entrepreneurship program for students aims to increase the motivation and entrepreneurial attitudes of Unsoed Purwokerto students. Business assistance activities carried out to 27 business groups, with a total of 81 student participants. Business assistance is carried out in the classroom and at the place of business. Assistance in class is done by describing the results of the work that has been done by business groups and discussion of problem solving. Assistance at the place of business is carried out by direct field visits at the business places of the business groups. The head of the business group directly explains the production process and conveys the constraints and problems experienced during production. The accompanying lecturer conducts a discussion in solving problems with business groups in the business place. Business assistance for students in conducting entrepreneurship can improve students motivation and attitude in working to run a business.